2021
DOI: 10.3389/fpubh.2021.657422
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Duration Is Associated With Domain-Specific Improvements in Cognitive Performance in 9–10-Year-Old Children

Abstract: Significant immunological, physical and neurological benefits of breastfeeding in infancy are well-established, but to what extent these gains persist into later childhood remain uncertain. This study examines the association between breastfeeding duration and subsequent domain-specific cognitive performance in a diverse sample of 9–10-year-olds enrolled in the Adolescent Brain Cognitive Development (ABCD) Study®. The analyses included 9,116 children that attended baseline with their biological mother and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
4
13
0
Order By: Relevance
“…Contrary to our hypotheses, breastfeeding history did not predict inhibitory control or EF in 3-year-olds. These results are in line with the results from Belfort et al (2016) [ 19 ], and Lopez et al (2021) [ 20 ], who also found no evidence for an association between breastfeeding and executive functioning. Contrarily, Julvez et al (2007) [ 18 ] found that breastfeeding was associated with high levels of observed EF in a sample of 500 4-year-old children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Contrary to our hypotheses, breastfeeding history did not predict inhibitory control or EF in 3-year-olds. These results are in line with the results from Belfort et al (2016) [ 19 ], and Lopez et al (2021) [ 20 ], who also found no evidence for an association between breastfeeding and executive functioning. Contrarily, Julvez et al (2007) [ 18 ] found that breastfeeding was associated with high levels of observed EF in a sample of 500 4-year-old children.…”
Section: Discussionsupporting
confidence: 92%
“…However, while one prospective longitudinal study including 500 preschoolers found that EF (assessed by validated questionnaires) was better when they were breastfed longer [ 18 ], another prospective longitudinal study including 180 children found no relation between breastfeeding and EF (assessed with cognitive tests) in 6- to 7-year-old children [ 19 ]. Additionally, a recent cross sectional study by Lopez et al (2021) also found no evidence for an association between breastfeeding and executive functioning (assessed with cognitive tests) in 9,116 9-10-year-old children [ 20 ]. To our knowledge, no study has specifically examined associations between breastfeeding history and inhibitory control in 3-year-olds.…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding promotes the achievement of early childhood milestones (language, cognition, fine motor skills, etc.) [ 5 , 6 ], and previous studies have identified the role of breastfeeding in neurodevelopment among newborns [ 7 , 8 , 9 , 10 ]. However, the associations between breastfeeding and ASD have remained unclear ( Table S1 in Supplementary Materials) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, previous studies have reported beneficial effects of breastfeeding on cognition, 1 including one study based on the ABCD dataset. 24 According to the results of an experimental intervention, the largest cognitive differences are found in verbal measures. 58,59 While we indeed observed a relationship between breastfeeding duration and cognition (including verbal cognition), it is somewhat striking that we did not find this relationship to be mediated by the left POrb/lOFC cluster, since it includes regions—particularly the pars orbitalis, which is part of the inferior frontal gyrus—that are recognized as being implicated in verbal functions.…”
Section: Discussionmentioning
confidence: 99%